Macroscopic and Microscopic Characterization of the Effect of “Activation” Process on the Performance of Buton Rock Asphalt-Modified Asphalt - Yafei Li; Meng Guo; Xu Liu (Advances in Materials Science and Engineering)
In the process of using Buton rock asphalt- (BRA-) modified asphalt, in order to improve the utilization rate of Buton rock asphalt and the performance of the modified asphalt, this paper puts forward the process of “activation” treatment of Buton rock asphalt, that is, grinding and heating of BRA to make natural asphalt precipitate. Laboratory tests show that compared with modified asphalt without activation process, the penetration of the modified asphalt decreases, the softening point rises, the ductility at 5°C and the kinematic viscosity at 135°C all have been increased, and the performance of the modified asphalt increases with the increase of the content of activated BRA. In order to further clarify the effect of “activation” process on the properties of BRA-modified asphalt from microlevel, atomic force microscopy (AFM) was used to test the microproperties of Buton rock asphalt before and after activation. It is found that the Derjaguin–Muller–Toporov (DMT) modulus of the modified asphalt is about 2.5 times that of base asphalt, which indicates that the viscous degree of modified asphalt with activated BRA has been greatly increased and the modification effect is remarkable.